A Rare Case of Huge Intraabdominal Mesenteric Cyst in a Paediatric Patient Mimicking Volvulus. - Yusuf, Marlina; Haron, Juhara (International Journal of Human and Health Sciences (IJHHS), 2019)
Mesenteric cyst is a very rare disease in children that can present in many various conditions. Its diagnosis is very challenging either by a clinical or imaging. Delay in diagnosis can cause significant morbidity and mortality for the patient. Hence, we shared a case of a huge mesenteric cyst in paediatric that presented as an acute abdomen and causing preoperative diagnostic dilemma. International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 175-177